The TASTY Locus on Chromosome 1 of Arabidopsis Affects Feeding of the Insect Herbivore Trichoplusia ni - Jander, Georg (American Society of Plant Physiologists, 2001)
The generalist insect herbivore Trichoplusia ni (cabbage looper) readily consumes Arabidopsis and can complete its entire life cycle on this plant. Natural isolates (ecotypes) of Arabidopsis are not equally susceptible to T. ni feeding. While some are hardly touched by T. ni, others are eaten completely to the ground. Comparison of two commonly studied Arabidopsis ecotypes in choice experiments showed that Columbia is considerably more resistant than Landsberg erecta. In no-choice experiments, where larvae were confined on one or the other ecotype, weight gain was more rapid on Landsberg erecta than on Columbia. Genetic mapping of this difference in insect susceptibility using recombinant inbred lines resulted in the discovery of the TASTY locus near 85 cM on chromosome 1 of Arabidopsis. The resistant allele of this locus is in the Columbia ecotype, and an F(1) hybrid has a sensitive phenotype that is similar to that of Landsberg erecta. The TASTY locus is distinct from known genetic differences between Columbia and Landsberg erecta that affect glucosinolate content, trichome density, disease resistance, and flowering time.